How AI-related drivers stimulate digital social entrepreneurship: An integrated framework of entrepreneurial event model within stimulus-organism-response theory - Cong Doanh Duong; Ta Van Loi; Thanh Hieu Nguyen (Digital Business, 2025)
Drawing on an integrated framework of the Entrepreneurial Event Model (EEM) and the Stimulus-Organism-Response (SOR) theory, this study investigates how AI-driven stimuli-specifically ChatGPT adoption and perceived AI competencies-influence individuals' cognitive perceptions (perceived feasibility and perceived desirability) and, in turn, their intentions to engage in digital social entrepreneurship. Employing a stratified sample of 986 students in Vietnam, we applied multiple linear regression and response surface analysis to test the proposed hypotheses. Findings reveal that both ChatGPT adoption and perceived AI competencies positively impact perceived feasibility and desirability, which independently and interactively drive intentions toward digital social entrepreneurship. Moreover, the congruence and imbalance between feasibility and desirability significantly shape entrepreneurial intentions. This research contributes by advancing an integrated EEM-SOR framework, offering new insights into how cognitive mechanisms operate in AI-driven digital social entrepreneurship. Practical recommendations are proposed for social entrepreneurs, educators, and policymakers seeking to foster AI-enabled social ventures.
Keywords: 650; ChatGPT adoption in entrepreneurship; Intention toward digital social entrepreneurship; Perceived AI competencies; Perceived desirability; Perceived feasibility